Development Aspects of Business Embroidery Craft Enni Design in Bukittinggi - Ratni Prima Lita; Meuthia Meuthia; Surya Sari; Debi Shintya Dewi (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
Community service Carried out at Enni Design in the city of Bukittinggi aims to expand the business by paying attention to aspects such as production, products, management, human resources, and facilities. Enni Design's business is expected to be Able to Increase product differentiation from competitors, improve HR capabilities in designing motifs and colors that follow fashion trends, improve human resource capabilities in preparing financial reports, and Utilize waste valuable economically. After training and innovation practices, businesses are given the opportunity to consult or discuss existing business opportunities and design strategies. The results of the training of partners show that they are Able to understand what differentiates Reviews their products Compared to competitors. In addition, it is also able to compile financial reports in accordance with accounting principles, and can manage waste into new products that are worth selling.